2004
DOI: 10.1097/00002508-200405000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Electro-Acupuncture and Hydrotherapy, Both in Combination With Patient Education and Patient Education Alone, on the Symptomatic Treatment of Osteoarthritis of the Hip

Abstract: In conclusion, EA and hydrotherapy, both in combination with patient education, induce long-lasting effects, shown by reduced pain and ache and by increased functional activity and quality of life, as demonstrated by differences in the pre- and post-treatment assessments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(82 citation statements)
references
References 26 publications
1
81
0
Order By: Relevance
“…While many of these studies directly use the term ‘dry needling’,5,18,21,26,33,56,64,67,104,110 in their methodology, other studies use alternative terminology such as ‘deep dry needling’,67 ‘superficial dry needling’,55,128 ‘TrP acupuncture’,20,80 ‘paraspinal needling’,64 ‘intramuscular and nerve root needling’,65 ‘needle electrical intramuscular stimulation’,129 ‘needle release’,113 ‘acupuncture needling’,63,113 ‘needling therapy’,17 ‘acupuncture’36–38,40,41,47,49–55,61,69,72,8188,90,92,94100,105108,112,115117,119123,130135 and ‘electroacupuncture’ 37,46,93,126,127,136139. Some studies have even chosen to use both ‘acupuncture and dry needling’19,23,24,62,77 in their titles.…”
Section: Trp Needling Is Only One Kind Of Dry Needlingmentioning
confidence: 99%
“…While many of these studies directly use the term ‘dry needling’,5,18,21,26,33,56,64,67,104,110 in their methodology, other studies use alternative terminology such as ‘deep dry needling’,67 ‘superficial dry needling’,55,128 ‘TrP acupuncture’,20,80 ‘paraspinal needling’,64 ‘intramuscular and nerve root needling’,65 ‘needle electrical intramuscular stimulation’,129 ‘needle release’,113 ‘acupuncture needling’,63,113 ‘needling therapy’,17 ‘acupuncture’36–38,40,41,47,49–55,61,69,72,8188,90,92,94100,105108,112,115117,119123,130135 and ‘electroacupuncture’ 37,46,93,126,127,136139. Some studies have even chosen to use both ‘acupuncture and dry needling’19,23,24,62,77 in their titles.…”
Section: Trp Needling Is Only One Kind Of Dry Needlingmentioning
confidence: 99%
“…With regards specifically to Hip OA, the review identified three trials evaluating the use of acupuncture in management of hip OA, one of which was evaluating the use of electro acupuncture as opposed to the traditional needle methods [21][22][23]. However, the studies were deemed to be too heterogenous to be included in a meta-analysis.…”
Section: Acupuncturementioning
confidence: 99%
“…Recommended modalities specific to hip OA include manual therapy, exercise program, hydrotherapy, electro-acupuncture, acupuncture with advice and home exercises. There is, however, 'insufficient evidence' to support exercise as a treatment to decrease pain or to improve function [11,[27][28][29][30][31]. The use of AposTherapy in the present study showed significant improvement in the subjective reports of pain and function after twelve weeks, as demonstrated by the significant improvement in the selfevaluation symptoms and QoL assessment questionnaires, as well as in the significant improvement in gait patterns.…”
Section: Discussionmentioning
confidence: 55%